WORD-FORMATION PRODUCTIVITY IN ENGLISH AND UZBEK: TYPOLOGICAL PARALLELS AND DIFFERENCES (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article examines the productivity of word-formation processes in English and Uzbek from a typological perspective and analyzes how structural, morphological, and semantic factors shape the creation of new lexical items in each language. Although both languages show constant lexical expansion driven by social, technological, and cultural change, their word-formation systems reflect distinct typological profiles. English, with its analytic structure and flexible compounding, demonstrates high productivity in derivation and blending. Uzbek, a member of the Turkic agglutinative family, displays strong suffixation patterns, stable morphological transparency, and predictable semantic shifts. The comparison reveals not only similarities but also key differences in how the two languages innovate lexically, and highlights the interplay between linguistic typology and creativity. The study concludes that understanding these parallels and divergences provides valuable insight for language teaching, translation, and linguistic research.